2019
DOI: 10.1088/2053-1591/ab4b03
|View full text |Cite
|
Sign up to set email alerts
|

Silicon micromachining with nanometer-thin boron masking and membrane material

Abstract: Chemical-vapor-deposition (CVD) conditions were investigated for enabling the growth of pure boron (PureB) on Si with low stress and at as low as possible temperature. The application of the B as masking material for Si wet etching by tetramethyl ammonium hydroxide (TMAH) and as membrane material was demonstrated for B deposition temperatures down to 300 °C. Layer thickness in the range 4 nm to 40 nm was applied. In a Si epitaxy reactor system a close to zero-stress condition was found at ∼600 °C, and in an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The targeted B-layer thickness was 3 nm, which was checked by HRTEM. Using spectroscopic ellipsometry as described in [20], the thickness of the B-layer was found to be 2.85 nm with a roughness of 1.97 nm, which are typical values for layers grown at 450°C. Previous work has shown that this roughness is associated with a less compact B-composition than that of layers grown at higher temperatures [20].…”
Section: Theoretical Considerationsmentioning
confidence: 91%
See 1 more Smart Citation
“…The targeted B-layer thickness was 3 nm, which was checked by HRTEM. Using spectroscopic ellipsometry as described in [20], the thickness of the B-layer was found to be 2.85 nm with a roughness of 1.97 nm, which are typical values for layers grown at 450°C. Previous work has shown that this roughness is associated with a less compact B-composition than that of layers grown at higher temperatures [20].…”
Section: Theoretical Considerationsmentioning
confidence: 91%
“…At 450°C, the B surface roughness is higher, about 1 nm, and the compactness lower [20], and at least 3 nm was needed for Al barrier purposes. Since this layer is of great interest as a back-end CMOS-compatible deposition, it was chosen here as a ''worst case'' layer for testing the barrier potentials of B with respect to Au and Cu.…”
Section: Introductionmentioning
confidence: 99%
“…B-membranes would also have many of these advantages: B has an even lower atomic number than C and the CVD layers are conductive, albeit with very high resistivity. Also, for application as membranes, an important advantage with respect to graphene is that B thin films are highly manufacturable [18,43,44]. The XUV group at University of Twente was also devoting some time to studying boron as a material for capping EUV pellicles for EUV lithography systems [45].…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…For the PureB photodiodes operated at room temperature (RT), the lowest dark currents and most robust B thin films are achieved by depositing the B-layer at 700 • C. Devices incorporating these B-layers have been commercialized as PureB detectors for low-energy electrons [11], [12] and vacuum ultraviolet/near-ultraviolet (VUV/NUV) light [10], [13]. The attraction for these applications lies in the extremely shallow junction depth and low dark currents, combined with exceptional optoelectronic stability and chemical robustness [14]- [16]. The latter is due to the strength of the B-B bonds that even for these amorphous thin films provide resistance to many chemical etchants and cleaning methods used in Si processing and detector maintenance [10], [16].…”
Section: Introductionmentioning
confidence: 99%
“…The attraction for these applications lies in the extremely shallow junction depth and low dark currents, combined with exceptional optoelectronic stability and chemical robustness [14]- [16]. The latter is due to the strength of the B-B bonds that even for these amorphous thin films provide resistance to many chemical etchants and cleaning methods used in Si processing and detector maintenance [10], [16]. The optoelectrical stability is largely due to the B-Si bonds that form a monolayer of fixed negative charge, enough to attract a high concentration of holes to the interface.…”
Section: Introductionmentioning
confidence: 99%